Birth of a killer - Shan, Darren (Shan, Darren. Saga of Larten Crepsley, 2011)
When his cousin is murdered at the factory where they both work as child laborers, young Larten Crepsley commits a horrific act and must live on the run until he meets a vampire named Seba Nile who offers him protection and training as a vampire's assistant.